Avaliação do fibrinogênio como uma nova fonte para a formação in vitro de produtos proteicos de oxidação avançada - Torbitz, Vanessa Dorneles (2015)
Oxidative stress is characterized by an imbalance between the production of free radicals, particularly reactive oxygen species (ROS), and the defense capacity of the organism against these species, leading to a progressive oxidative damage. Proteins are considered to be the primary target for oxidative damage, since they are major components of biological systems and may neutralize 50 to 75% of free radicals. Recently, a new class of compounds formed as a result of oxidative stress was described, referred to as advanced oxidation protein products (AOPP). The accumulation of AOPP was first described in patients with chronic renal failure on hemodialysis and subsequently it was found that this marker is involved in a number of pathological conditions such as diabetes, atherosclerosis, obesity, and acute renal failure. Previous studies have identified AOPP as a new marker of oxidative damage to proteins and a new class of inflammatory mediators promoting effects both at the cellular level, as at systemic level. In this context, different biological structures, including plasma proteins such as albumin and fibrinogen are susceptible to oxidation by ROS. It is known that albumin is the major target of oxidative stress in plasma of uremic patients, however, it has been demonstrated that the fibrinogen is also capable of undergoing oxidative modification. Whereas the oxidative and inflammatory processes are involved in the pathophysiology of a number of clinical conditions and AOPP is a biomarker which can reflect these changes, it is extremely important to evaluate the susceptibility of other proteins to the formation of these products, in addition to albumin. Thus, the aim of this study was to investigate the formation of AOPP from the fibrinogen in an in vitro model and evaluate structural and functional changes in the molecule of this pro-coagulant protein. Thus, to promote in vitro AOPP, fibrinogen was exposed to hypochlorous acid (HOCl) at various concentrations (1, 2 and 4 mM). After checking the effectiveness of fibrinogen to produce AOPP, was demonstrated that the formation of these products promotes functional alterations in fibrinogen, causing changes in their structural domains and increasing their procoagulant activity. Therefore, the fibrinogen can be considered a source of AOPP formation and deterioration caused by this process in the molecule of this protein, may be related to several pathological conditions involving coagulation system and contribute especially in the development of thrombotic processes.